Study on alteration of traditional Malay house in Kampung Banda Kaba, Melaka / Rohaslinda Ramele @ Ramli, Zarina Isnin (Ithnin) and Izatul Lailijabar - Ramele @ Ramli, Rohaslinda; Isnin (Ithnin), Zarina; Lailijabar, Izatul (Research Management Institute (RMI), 2010)
Recently, conservation has become an important agenda in heritage cities like Malacca and Penang, since they have been gazetted as Historic Cities at the Straits of Malacca in the UNESCO World Heritage List on July 2008. Government, private and charitable organizations are taking part in conserving and preserving the heritages. However, in Malacca Historical City, related legislations are not strictly being enforced in some areas of Buffer Zone, bringing issues to the historical environment and negligence to kampung areas; the traditional housing groups, in the city. Due to modernization and urbanization of the surrounding area of Malacca City, the traditional Malay houses in the kampung areas are exposed to alteration whether on their materials, structure, spatial usage and design. Efforts to protect the houses by the residents are limited to their financial, ages and skills to maintain, reuse, rebuilt or repair the houses. Selling and moving out has been the final solution due to incapability of owners to afford maintenance cost, and needs for instant cash. Alteration also occurs in terms of use, as in the case of traditional space which no longer use as residential usage. Rebuilding demands traditional building techniques and craft skills which have long been declining. The repair often uses affordable new materials such as zinc plate and laminated-wood panel. This study illustrates the present situation of urban conservation in Malacca along with the urban morphology, focusing on Buffer Zone areas. Kampung Banda Kaba is chosen as a study field representing kampung areas in Buffer Zone; which contains 56 houses that can still be identified as Malacca long-roofed houses. The objectives of this study are to reveal the characteristics of Malacca long-roofed houses, to investigate the alteration problems on Malacca long-roofed houses in Kampung Banda Kaba and to propose solutions and new conservation guidelines for Malacca long-roofed houses in Buffer Zone area. The findings of this research offered a better environment of Kampung Banda Kaba as a 'Traditional Malay Kampung' in Malacca Historical City, revision of the existing conservation guidelines for Buffer Zone towards redevelopment and integration of traditional houses and promotion of tourism development in Kampung Banda Kaba and the whole Buffer Zone areas.